Festival Lima Gunung Magelang Performances in the Covid-19 Pandemic Era - Bahtiar Arbi; Muhammad Jazuli; Wadiyo Wadiyo; Agus Cahyono (International Conference on Science, Education, and Technology, 2021)
Lima Gunung Community is a forum for traditional artists in the five mountains of Magelang, Central Java, Indonesia. The five mountains are Mount Merapi, Merbabu, Andong, Sumbing, and Menoreh. Sutanto Mendut founded the Lima Gunung Community to preserve traditional arts, especially those in the Lima Gunung area. Almost all of the arts in the villages are an integral part of the implementation of local rituals. Traditional arts that are ritualistic are preserved in their original form, while other arts that are entertainment are modified in such a way as to be contemporary. This contemporary art tradition is expected to exist and not become extinct like other traditional arts that do not adapt to the present. Lima Gunung Festival is a place for artistic expression for village artists and suggests contemporary traditional arts. Lima Gunung Festival 2020 and 2021 will be held online due to the COVID-19 pandemic. Lima Gunung Festival is broadcast through the youtube channel where the event is held suddenly to avoid crowds. The research method used is qualitative with an interdisciplinary approach using ethnomusicology, sociology, education, and philosophy. The results of this study are expected to provide local wisdom values, educational values, and cultural values ​​during the COVID-19 pandemic situation in Indonesia.